THE EFFECT OF WORK ENVIRONMENT AND INDIVIDUAL CHARACTERISTICS ON MEDICAL MEDICAL EMPLOYEE PERFORMANCE AT PT SARI TANI SUMATRA - Maurizio Zanardi; Jprge O.Brusa (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
In this data collection method, they make their own observations in the field, the implementation is in the form of a direct survey. The population in this study were customers of the Buana Water refill drinking water depot in the city of Indrapura with a population of 80 based on the number of customers per month. Because the total population is less than 100 people, the sampling technique used is the census method where the entire population of 80 regular customers will be used as a sample that has the characteristics of making purchases more than 2 times. The results of the research on the first hypothesis are accepted, meaning that the Service Quality Variable (X1) has a positive and significant effect on the Customer Satisfaction Variable (Y). the second hypothesis is accepted, meaning that the Price Variable (X2) has a positive and significant effect on the Customer Satisfaction Variable (Y). the third hypothesis is accepted, meaning that the Service Quality Variable (X1), Price Variable (X2) have a significant simultaneous effect on the Customer Satisfaction Variable (Y).